2012
DOI: 10.1073/pnas.1200603109
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-sensing agr mediates bacterial oxidation response via an intramolecular disulfide redox switch in the response regulator AgrA

Abstract: Oxidation sensing and quorum sensing significantly affect bacterial physiology and host-pathogen interactions. However, little attention has been paid to the cross-talk between these two seemingly orthogonal signaling pathways. Here we show that the quorum-sensing agr system has a built-in oxidation-sensing mechanism through an intramolecular disulfide switch possessed by the DNA-binding domain of the response regulator AgrA. Biochemical and mass spectrometric analysis revealed that oxidation induces the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 41 publications
3
91
0
1
Order By: Relevance
“…The success of the bacterium in pathogenesis is mainly attributed to its sophisticated signaling and response systems, including global transcriptional regulators, and various two-component systems, which the bacterium uses to sense a variety of signals and environmental stimuli (28)(29)(30)(31)(32)(33)(34). Despite the recognized importance of quinone in cellular processes, its role in bacterial gene regulation and signal transductions in human pathogens remains elusive.…”
Section: Molecular Mechanism Of Quinone Signaling Mediated Through S-mentioning
confidence: 99%
“…The success of the bacterium in pathogenesis is mainly attributed to its sophisticated signaling and response systems, including global transcriptional regulators, and various two-component systems, which the bacterium uses to sense a variety of signals and environmental stimuli (28)(29)(30)(31)(32)(33)(34). Despite the recognized importance of quinone in cellular processes, its role in bacterial gene regulation and signal transductions in human pathogens remains elusive.…”
Section: Molecular Mechanism Of Quinone Signaling Mediated Through S-mentioning
confidence: 99%
“…As a possible oxidative sensor, LasR joins QS regulators AgrA (19) and SdiA (20), shown to have dual roles in both QS and oxidative sensing. The linking of quorum sensing to oxidative stress response through LasR may represent one of the traits that enables P. aeruginosa to coordinate growth and flourish under a variety of conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the recent finding that LasR may be governed by both oxidants and QS autoinducers, several other bacterial regulators have been linked to a similar dual function. Staphylococcus aureus AgrA has been shown to form an intramolecular disulfide bond within its DBD when oxidized, leading to a reduction in DNA binding affinity (19). Additionally, Escherichia coli SdiA, a LuxR homolog like LasR, forms an intermolecular disulfide bond within its DBD, covalently linking two monomers and altering promoter binding affinity when oxidized with the addition of 2 mM H 2 O 2 in EMSAs (20).…”
mentioning
confidence: 99%
“…We previously showed that, at the molecular level, the reactive oxygen species found in CS downregulate the expression of a quorumsensing regulon, agr, while inducing genes encoding a variety of surface proteins involved in biofilm formation and host cell adherence (11). The agr regulon is a redox sensor that regulates global transcription, including the regulation of the staphylococcal virulome and biofilm dispersal (33,34). Based on these observations, we sought to establish CSEinduced hypervirulence of the USA300 strain in a mouse model of acute pneumonia and to identify CSE-mediated alterations in genome-wide transcription using RNAseq.…”
Section: Discussionmentioning
confidence: 99%